Immune monitoring technology primer: immunosequencing. Issue 1 (25th June 2015) - Kirsch, Ilan
Abstract : Background: Profiling of the immune receptor repertoire is becoming increasingly relevant to the understanding and clinical management of cancer, autoimmunity, aging, and infectious disease. Findings: A platform technology is described that provides comprehensive immune receptor profiling. Conclusion: Immunosequencing is a platform technology that allows the enumeration, specification and quantification of each and every B-and/or T-cell in any biologic sample of interest. It is based on bias-controlled multiplex PCR and high throughput sequencing and is highly accurate, standardized, and sensitive.